A Complete Master, Expert Editor, and Outstanding Friend (Theological Kronos, 2021)
I receive with deep gratitude the invitation from the editors of Kronos Teológico to participate in this tribute to the teacher and friend, Dr. C. René Padilla. In my response to the invitation, I noted that this would be an affectionate reflection in which, through a testimonial style, I would express how René’s life and work influenced my own life and ministry as a theologian, pastor, and staff member of a Christian service organization.His life was devoted precisely to this: cultivating meaningful relationships and building friendships that enabled him to encourage new writers, support emerging ministries, and walk alongside individuals seeking ways to serve the kingdom of God in Latin America. A life invested in such a way leaves, beyond edited books or coordinated projects, living memories in those of us who today give thanks to the Lord for having had him as mentor, friend, and teacher.
Keywords: Affectionate reflection; mentor, friend, and teacher; theologian; pastor and staff member